2001
DOI: 10.1081/erc-100107866
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the H19 Gene in Sheep and Effect of Maternal Fasting on Its Expression in the Fetus

Abstract: Mapped on the same chromosome as the Insulin-like Growth Factor II (IGF-II), an important factor regulating fetal growth, the H19 gene, is believed to play a role during embryogenesis and to share similar regulatory elements with IGF-II possibly by an enhancer competition system. This study was designed to characterize the ontogeny of H19 in sheep and the effect of maternal fasting on the expression of fetal IGF-II and H19 mRNA. A partial cDNA clone for the ovine H19 gene was isolated and used as a probe for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Tongue RNA from the control animals was also analysed. H19 was expressed at high levels in the tongue of all the lambs, confirming earlier reports on high expression in neonates (Naimeh et al, 2001;Lee et al, 2002), but levels appeared unaltered in the cloned lambs. IGF2 expression was relatively high and appeared to be similar in cloned and control animals.…”
Section: Analysis Of H19 and Igf2r In Lambs Derived By Nuclear Transfersupporting
confidence: 91%
See 1 more Smart Citation
“…Tongue RNA from the control animals was also analysed. H19 was expressed at high levels in the tongue of all the lambs, confirming earlier reports on high expression in neonates (Naimeh et al, 2001;Lee et al, 2002), but levels appeared unaltered in the cloned lambs. IGF2 expression was relatively high and appeared to be similar in cloned and control animals.…”
Section: Analysis Of H19 and Igf2r In Lambs Derived By Nuclear Transfersupporting
confidence: 91%
“…The sheep H19 gene was also found to have the same exon -intron structure as in primates and rodents. The conservation of the H19 gene amongst different mammalian groups, and its similar pattern of expression during ovine and murine development (Sasaki et al, 1995;Naimeh et al, 2001;Lee et al, 2002), suggests that the non-coding H19 RNA is functional (Hurst and Smith, 1999). Although H19 RNA seems not to have an essential role in mouse development (Jones et al, 1998), several studies indicate that it might function in regulating the translation of other, coding RNAs, possibly even that of IGF2 (Li et al, 1998;Runge et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Fetuses from mouse embryos cultured in the presence of serum had 31 and 15% reduction in H19 and Igf2 respectively compared with in vivo counterparts (Khosla et al 2001b). In addition, fetal liver from pregnant ewes fasted for 48 h showed a 61% reduction in H19 without any alteration in IGF2 expression (Naimeh et al 2001). It is possible that the expression of H19 and Igf2 are regulated independently under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The level of IGF2 protein can also be regulated by IGF2R (Lau et al 1994). Previously, studies have shown that H19 is very sensitive to preimplantation culture condition (Doherty et al 2000, Lane & Gardner 2003, Mann et al 2004) and maternal dietary restriction altered H19 and IGF2 gene expression in fetal sheep (Brameld et al 2000, Naimeh et al 2001. The culturing of sheep embryos to blastocyst stage led to reduction in IGF2R transcript and protein in late gestation (Young et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[158][159][160] Interestingly, similar alterations in the expression of the imprinted genes H19 and IGF2 has also been reported to occur in fetal sheep due to maternal LPD during the preimplantation period. 161 Given that maternal undernutrition can lead to alteration in steroid hormone levels, 162,163 this may in turn affect H19 and/or IGF2 gene expression. Fowden and Forhead 164 highlighted the potential role of hormones as epigenetic signals in determining the phenotypical outcome of environmental cues acting during intrauterine development, as hormones signal the type, severity and duration of the environmental cue to the developing feto-placental tissues.…”
Section: Underlying Mechanisms: the Role Of Epigeneticsmentioning
confidence: 99%